High-performance GWCF-coated PEEK composite material constructed by hybridized heterogeneous fiber filler and preparation method of high-performance GWCF-coated PEEK composite material
By plating nickel on the carbon fiber surface and building a hybrid network of graphene and carbon nanotubes, GW&CF@PEEK composite materials with excellent thermal conductivity, electrical conductivity and electromagnetic shielding properties were prepared, which solved the CFRP composite materials under lightning strikes and extreme weather conditions. Security Question.
Patent Information
- Application Number
- CN202411632497.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
Existing CFRP composite materials are susceptible to electromagnetic interference and insufficient conductivity under lightning strikes and extreme weather conditions, resulting in threats to flight safety.
By plating nickel on the surface of the carbon fiber and building a hybrid network of graphene and carbon nanotubes on its surface, a hybrid heterofiber filler is formed to prepare GW&CF@PEEK composites.
The thermal conductivity, electrical conductivity, electromagnetic shielding performance and electrical heating capability of the composite material are significantly improved, while maintaining mechanical properties, solving the problems of insufficient conductivity and electromagnetic interference.
Smart Images

Figure CN119505513A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials, and in particular to a high-performance GW&CF@PEEK composite material constructed with a hybrid heterogeneous fiber filler and a preparation method thereof. Background Art
[0002] With its outstanding specific strength, high corrosion resistance and unique design flexibility, carbon fiber reinforced polymer composites (CFRP) have been enthusiastically used in aerospace, transportation, energy, electronic equipment and sports fields, which are very eager to reduce weight without sacrificing performance. In recent decades, with the development of advanced manufacturing technology, advanced composite materials have been rapidly developed. Among them, carbon fiber reinforced polymer (CFRP) composites have been widely used in aerospace applications due to their light weight, excellent mechanical properties, fatigue resistance and corrosion resistance. The weight percentage of CFRP composites in civil aircraft has become an important indicator for evaluating the progress of aircraft. The weight percentage of composites in new generation civil aircraft such as Boeing 787 and Airbus A350 has exceeded 50%. In particular, CFRP composites are mainly used as large main load-bearing structures such as fuselages and wings. The large-scale use of high-strength and lightweight CFRP composites in civil aircraft can effectively increase passenger capacity and fuel efficiency. However, as a semiconductor material, CFRP composites are susceptible to accidental lightning strikes compared with metal materials, which may bring some harmful problems such as electromagnetic interference (EMI) and direct damage to CFRP composites by lightning strikes. Over the years, the aviation industry has increasingly adopted carbon fiber reinforced polymer (CFRP) composites to reduce weight and improve mechanical properties. However, a number of major issues have emerged that have hindered the widespread use of CFRP composites. Among these issues, the need to significantly improve electrical and thermal conductivity is critical. Such deficiencies pose an important threat to flight safety, especially during extreme weather conditions such as lightning strikes and icing. Although carbon fiber has excellent inherent conductivity, the insulating properties of the resin matrix can compromise the overall conductivity during a lightning strike, leading to destructive consequences such as acoustic shock waves, resin pyrolysis, fiber sublimation, and even composite combustion. In addition, the electromagnetic pulse generated by lightning strikes poses a serious risk to electronic equipment, further endangering flight safety. On average, lightning strikes occur once every 3,000 flight hours, coupled with frequent icing, and there is an urgent need to develop an innovative CFRP composite with enhanced electrical conductivity, effective electromagnetic interference (EMI) shielding, and electrical heating (E-heating) capabilities.
[0003] Another potential risk to flight safety comes from electromagnetic interference, which can interfere with delicate electronic instruments in aircraft, such as onboard radar or navigation systems, due to the low impedance mismatch between the CFRP skin and the air environment. Therefore, considering issues related to lightning strike protection (LSP) and electromagnetic interference (EMI) shielding is extremely important to meet the protection requirements for flight safety, especially for these modern aircraft that use CFRP on a large scale. Carbon fiber reinforced polymer (CFRP) has also received widespread attention in aerospace applications due to its high specific strength, light weight, easy processing, low thermal expansion, ablation resistance and high thermal conductivity.
[0004] Traditionally, researchers have focused on a single aspect of CFRP, such as improving its mechanical properties, its conductive composites, enhancing EMI shielding operations, or developing electronic heating solutions. The consequences of neglecting EMI shielding and electronic heating capabilities are evident in historical aviation accidents, emphasizing the need for comprehensive research on conductivity, EMI shielding, and electronic heating performance to ensure flight safety. Recent studies have shown that improving conductivity and optimizing material structure can effectively mitigate the effects of EMI. Given the connection between electronic heating and electrical pathways, creating a complex conductive network in the designed structure is expected to not only improve conductivity, but also mitigate electromagnetic interference (EMI) shielding and attribute electronic heating capabilities.
[0005] Simple carbon fibers dispersed in polymers generally offer a good balance between mechanical and electrical properties compared to metallic fillers. It is generally accepted that both conductivity and EM shielding effectiveness increase as the percentage of conductive carbon fiber content increases. At very low filler concentrations, the conductivity remains close to that of the pure polymer because the distances between the conductive elements are too large to form a conductive network and the current flows only through the conductivity between the conductive elements. These sparsely distributed elements interact with electromagnetic waves and provide little shielding. When the filler concentration reaches the percolation threshold, a conductive network is formed. This results in a rapid increase in conductivity of several orders of magnitude over a very narrow range of fiber concentrations. With further addition of conductive fillers, the conductivity levels off. However, after the percolation threshold is reached, the EM shielding effectiveness increases more significantly. Composites with a newly formed conductive network have some perforations through which electromagnetic energy can leak. Adding more conductive particles means that the conductive network becomes denser, resulting in a closed structure of the network that is not affected by electromagnetic leakage. The EM shielding effectiveness in such a structure tends to increase slightly with increasing frequency. As the wavelength decreases and approaches the size of the optical fiber, the electromagnetic wave is more likely to encounter the fibers in the polymer, and the optical fiber is more likely to absorb or reflect the electromagnetic wave. At very high carbon fiber concentrations, the weak frequency dependence is attributed to enhanced reflection from multiple coherent scatterers.
[0006] One of the problems with using pure discontinuous carbon fibers as conductive fillers is that a relatively large amount of carbon fibers is usually required to achieve a high level of shielding. However, one of the problems with carbon fibers as conductive fillers is that a large amount of carbon fibers is usually required to achieve the desired performance, which increases the weight and cost of the composite material and also causes dispersion difficulties. Below the percolation threshold of the filler, the distance between the conductive fillers is too large to form a conductive network, so the conductivity remains close to that of the pure polymer.
[0007] However, high filler content poses difficulties for commonly used manufacturing techniques (such as extrusion or injection molding) due to a significant decrease in toughness and rheological properties. Large amounts of carbon fibers increase the weight and cost of the composite and may also lead to difficulties in uniform dispersion. One solution is to add a thin layer of metal to the surface of the carbon fibers to enhance electron transport in the conductive network, improve conductivity, dielectric polarization, magnetic loss properties and interfacial interactions. Although this approach is promising, metals also have challenges such as excessive weight, susceptibility to corrosion and poor flexibility. In summary, although non-metallic carbon-based nanomaterials are lightweight and corrosion-resistant, they face challenges related to cost and safety, while another key issue is the compromised mechanical properties caused by the metallization of carbon fibers, which weakens the interfacial adhesion between the fiber and the matrix.
[0008] To address these challenges, different strategies have been explored, including incorporation of highly conductive nanofillers such as carbon nanotubes and graphene onto the carbon fiber surface via chemical grafting, sizing techniques, chemical vapor deposition (CVD), electrophoretic deposition (EPD), and layer-by-layer (LbL) attachment. In addition, electroplating and spraying techniques have also been used to introduce metal particles onto the CF surface and have shown potential for enhancing conductivity. Summary of the invention
[0009] In view of this, the present invention proposes a high-performance GW&CF@PEEK composite material constructed by hybrid heterogeneous fiber filler and a preparation method thereof.
[0010] The technical solution of the present invention is achieved in this way:
[0011] A method for preparing a high-performance GW&CF@PEEK composite material using a hybrid heterogeneous fiber filler comprises the following steps:
[0012] S1, heat-treating the carbon fiber, adding the heat-treated carbon fiber to a solution containing nickel sulfate, nickel chloride, boric acid and sodium dodecyl sulfate, and plating nickel to obtain nickel-plated carbon fiber;
[0013] S2, adding nickel-plated carbon fiber to benzoxazine / acetone solution, then adding graphene and carbon nanotubes and stirring, finally transferring to an oven for heat curing after obtaining a slightly moist state by vacuum filtration; after curing, a hybrid filler is obtained;
[0014] S3. The hybrid filler and polyetheretherketone are mixed and then hot-compression molded to obtain a GW&CF@PEEK composite material.
[0015] Further, in step S1, during nickel plating, the pH value of the plating solution is 7.5-8.5, the plating solution temperature is 60-70°C, and the current density is 1.2-1.7A / dm 2 , time is 3-8min.
[0016] Further, step S1, the preparation of the nickel-plated carbon fiber includes the following steps: before electroplating, firstly, heat-treating the carbon fiber in an air atmosphere at 440-460°C for 20-40 minutes; then, adding the pretreated carbon fiber to a solution containing 190-210 g / L nickel sulfate, 55-65 g / L nickel chloride, 45-55 g / L boric acid and 0.08-0.12 g / L sodium dodecyl sulfate; during nickel plating, the pH value of the plating solution is maintained at 7.8-8.2, the plating solution temperature is 60-70°C, and the current density is 1.4-1.6 A / dm 2 , time is 4-6min, to obtain nickel-plated carbon fiber.
[0017] Further, step S1, the preparation of the nickel-plated carbon fiber includes the following steps: before electroplating, firstly, heat-treating the carbon fiber in an air atmosphere at 450°C for 30 minutes; then, adding the pretreated carbon fiber to a solution containing 200 g / L nickel sulfate hexahydrate, 60 g / L nickel chloride hexahydrate, 40 g / L boric acid and 0.1 g / L sodium dodecyl sulfate; during nickel plating, the pH value of the plating solution is maintained at 8.0, the plating solution temperature is 65°C, and the current density is 1.5 A / dm 2 , time is 5min, and nickel-plated carbon fiber is obtained.
[0018] Further, step S2, the preparation of the hybrid filler includes the following steps: adding nickel-plated carbon fiber to a 0.8-1.2wt% benzoxazine / acetone solution, then adding graphene and carbon nanotubes and stirring for 5-7h, the total mass of graphene and carbon nanotubes is 0.95-1.05 times the mass of the nickel-plated carbon fiber, and the mass ratio of graphene to carbon nanotubes is 7-9:1.5-2.5, and finally transferring to an oven for thermal curing after obtaining a slightly moist state by vacuum filtration; the thermal curing procedure is: first thermal curing at 145-155°C for 1.5-2.5h, then thermal curing at 175-185°C for 1.5-2.5h, and finally thermal curing at 205-215°C for 1.5-2.5h; after curing, a hybrid filler is obtained.
[0019] Further, step S2, the preparation of the hybrid filler includes the following steps: adding nickel-plated carbon fiber to a 1wt% benzoxazine / acetone solution, then adding graphene and carbon nanotubes and stirring for 6 hours, the total mass of graphene and carbon nanotubes is the same as the mass of the nickel-plated carbon fiber, the mass ratio of graphene to carbon nanotubes is 8:2, and finally transferring to an oven for thermal curing after obtaining a slightly moist state through vacuum filtration; the thermal curing procedure is: first thermal curing at 150°C for 2h, then thermal curing at 180°C for 2h, and finally thermal curing at 210°C for 2h; after curing, a hybrid filler is obtained.
[0020] Further, in step S3, the temperature of the hot compression molding is 375-385°C, preferably 380°C.
[0021] Further, in step S3, the volume fraction of filler in the composite material is 1.8% to 35%, preferably 34.15%.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention constructs a hybrid heterogeneous fiber filler, which is a sub-millimeter fibrous filler, which can solve the problem of agglomeration of nanofillers in polymers and improve the problem of insufficient thermal conductivity and electrical conductivity of carbon fibers.
[0024] The present invention constructs a unique three-core-shell filler network structure based on carbon fiber (CF), combines metals and nanomaterials, and prepares cost-effective materials with excellent performance such as improved thermal conductivity, electrical conductivity, EMI shielding, electric heating and mechanical properties. The present invention first nickel-plated the carbon fiber surface to enhance the electron transmission in the conductive network, and then anchored the interconnected graphene / carbon nanotube (GnPs&MWCNTs) hybrid network on the Ni-CF surface through the thermal curing of benzoxazine, and constructed a hybrid three-dimensionally arranged thermal conductive network on the nickel-plated carbon fiber surface. These multi-scale carbon-based fillers with special 3D structures have been proven to be excellent candidates for improving the thermal conductivity of the entire layer of CF / PEEK composites. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 : Schematic diagram of the preparation method of the GW&Ni-CF@PEEK composite material according to an embodiment of the present invention;
[0026] Figure 2 : Scanning electron microscope image of carbon fiber;
[0027] Figure 3 : Scanning electron micrograph of nickel-coated carbon fiber;
[0028] Figure 4 : Scanning electron microscopy of hybrid heterogeneous fibrous fillers;
[0029] Figure 5 : Element distribution diagram of hybrid heterogeneous fiber filler;
[0030] Figure 6 : Comparison of thermal conductivity of PEEK composites doped with hybrid heterogeneous fiber fillers and mixed fillers;
[0031] Figure 7 : Comparison of electromagnetic shielding performance of PEEK composites doped with hybrid heterogeneous fiber fillers and mixed fillers;
[0032] Figure 8 : Comparison of the electrical conductivity of PEEK composites doped with hybrid heterogeneous fiber fillers and mixed fillers;
[0033] In the figure,
[0034] Thermal Conductivity: thermal conductivity;
[0035] EMI SE T : Electromagnetic shielding performance;
[0036] Electrical conductivity: electrical conductivity;
[0037] Filler Content (vol%): Volume fraction of filler. DETAILED DESCRIPTION
[0038] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0039] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0040] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0041] Table 1 Sources of some raw materials (manufacturers / brands)
[0042] Serial number raw material Manufacturer / Brand 1 Carbon Fiber (CF) Hebei Cangzhou Carbon Fiber Factory 2 Benzoxazine Chengdu Keyi Polymer Technology Co., Ltd. 3 acetone Sinopharm Chemical Reagent Co., Ltd. 4 <![CDATA[Nickel sulfate hexahydrate (NiSO4·6H2O)]]> Sinopharm Chemical Reagent Co., Ltd. 5 <![CDATA[Nickel(II) chloride hexahydrate (NiCl2·6H2O)]]> Sinopharm Chemical Reagent Co., Ltd. 6 <![CDATA[Boric acid (H3BO3)]]> Sinopharm Chemical Reagent Co., Ltd. 7 <![CDATA[Sodium dodecylbenzenesulfonate (C12H 25 SO4Na)]]> Shanghai MacLean Biochemical Technology Co., Ltd. 8 Polyetheretherketone (PEEK) Changchun Jida Special Plastic Engineering Research Co., Ltd.
[0043] Table 2 Chinese meaning of English
[0044] Serial number English Chinese 1 CF, Carbon Fiber Carbon Fiber 2 Ni-CF Nickel-plated carbon fiber 3 GnP Graphene 4 MWCNTs Carbon Nanotubes 5 PEEK Polyetheretherketone
[0045] Example
[0046] S1. Nickel is plated on the surface of carbon fiber by electroplating: Before electroplating, the carbon fiber (CF) is first heat-treated in an air atmosphere at 450°C for 30 minutes to remove the sizing agent. Then the pre-treated CF is added to a mixture containing NiSO4·6H2O (200 g / L), NiCl2·6H2O (60 g / L), H3BO3 (40 g / L) and C12H 25 SO4Na (0.1g / L) solution. When plating Ni, the pH value of the plating solution is maintained at 8.0, the plating temperature is 65℃, and the current density is 1.5A / dm 2 , time is 5min, and nickel-plated carbon fiber (Ni-CF) is obtained.
[0047] S2. Preparation of hybrid heterogeneous fiber filler. The nickel-plated carbon fiber prepared in step S1 is added to a 1wt% benzoxazine / acetone solution, followed by adding graphene (GnPs) and carbon nanotubes (MWCNTs) in a mass ratio of 8:2 and stirring for 6 hours. The total mass of graphene and carbon nanotubes is the same as that of the nickel-plated carbon fiber. Finally, it is transferred to an oven for thermal curing after being obtained in a slightly moist state by vacuum filtration. The thermal curing procedure is: 150℃ / 2h+180℃ / 1h+210℃ / 1h. After curing, a mixed graphene and carbon nanotube thermal conductive network is finally deposited on the surface of the nickel-plated carbon fiber, and the hybrid filler is recorded as GW&Ni-CF.
[0048] For comparison, a mixed graphene and carbon nanotube thermal conductive network loaded on the surface of carbon fiber was prepared, recorded as GW&CF (control group). Specific preparation method: Add carbon fiber CF to 1wt% benzoxazine / acetone solution, then add graphene (GnPs) and carbon nanotubes (MWCNTs) with a mass ratio of 8:2 and stir for 6 hours, finally transfer to an oven for thermal curing after obtaining a slightly moist state by vacuum filtration. The thermal curing procedure is: 150℃ / 2h+180℃ / 1h+210℃ / 1h. After curing, a mixed graphene and carbon nanotube thermal conductive network is finally deposited on the surface of carbon fiber, and the hybrid filler is recorded as GW&CF.
[0049] S3. Preparation of PEEK composite materials: Schematic diagram of preparation of composite materials with different structures as shown in Figure 1 shown.
[0050] The hybrid heterogeneous fiber filler GW&Ni-CF and polyetheretherketone (PEEK) particles prepared in step S2 were mixed in a certain mass ratio and hot compression molded using a flat plate vulcanizer at 380°C to obtain a series of composite materials with hybrid heterogeneous filler volume fractions of 1.81%, 3.76%, 8.07%, 13.09%, 18.98%, 26.00%, and 34.15%, which were recorded as GW&Ni-CF@PEEK composite materials.
[0051] For comparison, a series of composite materials randomly mixed with PEEK were prepared, including graphene, carbon nanotubes and nickel-plated carbon fibers (the total amount of graphene and carbon nanotubes was the same as that of nickel-plated carbon fibers, and the mass ratio of graphene to carbon nanotubes was 8:2), and the total filler content (by volume percentage) was 1.81%, 3.76%, 8.07%, 13.09%, 18.98%, 26.00%, and 34.15%, which were recorded as GnPs / MWCNTs / Ni-CF / PEEK composite materials as a comparison group.
[0052] The results show that the present invention successfully prepared a new type of fiber filler. This hybrid heterogeneous fiber filler can alleviate the stacking problem of nanofillers such as graphene and carbon nanotubes, and form a micron-scale filler interconnection network in the composite material. Compared with the composite material with randomly dispersed fillers, the composite material prepared by the present invention has higher thermal conductivity, electromagnetic shielding and electrical conductivity.
[0053] Figure 1 It is a preparation process for new hybrid heterogeneous fibers and composite materials.
[0054] Figure 2 : Surface morphology of the original CF, which has a smooth surface.
[0055] Figure 3 :and Figure 2 In comparison, there is a layer of nickel metal particles on the surface of nickel-plated carbon fiber, indicating that nickel is successfully plated on the smooth CF surface.
[0056] Figure 4 : Graphene and carbon nanotubes were fixed on the surface of nickel-plated carbon fiber using thermosetting benzoxazine to construct hybrid heterogeneous fiber fillers. The obvious attachment of graphene and carbon nanotubes can be seen in the figure, confirming that the new hybrid heterogeneous fiber was successfully prepared.
[0057] Figure 5 : The element distribution diagram of the hybrid heterogeneous fiber filler further confirms the composition of the hybrid heterogeneous fiber. Ni is mainly provided by nickel-plated carbon fiber, C is provided by graphene carbon nanotubes and nickel-plated carbon fiber and a small amount of benzoxazine, and N element is provided by benzoxazine.
[0058] Figure 6 : The thermal conductivity of PEEK composite materials doped with hybrid heterogeneous fiber fillers and mixed fillers. The comparison results show that the use of hybrid heterogeneous fiber fillers in the present invention is beneficial to constructing a thermal conductive path and improving thermal conductivity.
[0059] Figure 7 : The electromagnetic shielding performance of PEEK composite materials doped with hybrid heterogeneous fiber fillers and mixed fillers. The comparison results show that the use of hybrid heterogeneous fiber fillers in the present invention enhances the multiple reflection and absorption of electromagnetic waves and improves the electromagnetic shielding performance.
[0060] Figure 8 : The conductive properties of PEEK composite materials doped with hybrid heterogeneous fiber fillers and mixed fillers are compared. The results show that the use of hybrid heterogeneous fiber fillers in the present invention strengthens the construction of the conductive network and improves the conductive properties.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-performance GW&CF@PEEK composite material using a hybrid heterogeneous fiber filler, characterized in that: The following steps are involved: S1, heat-treating the carbon fiber, adding the heat-treated carbon fiber to a solution containing nickel sulfate, nickel chloride, boric acid and sodium dodecyl sulfate, and plating nickel to obtain nickel-plated carbon fiber; S2, adding the nickel-plated carbon fiber to a benzoxazine / acetone solution, then adding graphene and carbon nanotubes and stirring, finally transferring to an oven for heat curing after obtaining a slightly moist state by vacuum filtration; after curing, a hybrid filler is obtained; S3. After mixing the hybrid filler and polyetheretherketone, the mixture is subjected to hot compression molding to obtain a GW&CF@PEEK composite material.
2. The method for preparing the GW&CF@PEEK composite material according to claim 1, characterized in that: Step S1, during nickel plating, the pH value of the plating solution is 7.5-8.5, the plating solution temperature is 60-90°C, and the current density is 1.2-1.7A / dm 2 , time is 3-8min.
3. The method for preparing the GW&CF@PEEK composite material according to claim 1, characterized in that: Step S1, the preparation of the nickel-plated carbon fiber includes the following specific steps: before electroplating, firstly, heat-treating the carbon fiber in an air atmosphere at 440-460°C for 20-40 minutes; then, adding the pretreated carbon fiber to a solution containing 190-210 g / L nickel sulfate, 55-65 g / L nickel chloride, 45-55 g / L boric acid and 0.08-0.12 g / L sodium dodecyl sulfate; during nickel plating, the pH value of the plating solution is maintained at 7.8-8.2, the plating solution temperature is 60-70°C, and the current density is 1.4-1.6 A / dm 2 , time is 4-6min, to obtain nickel-plated carbon fiber.
4. The method for preparing the GW&CF@PEEK composite material according to claim 3, characterized in that: Step S1, the preparation of the nickel-plated carbon fiber includes the following specific steps: before electroplating, firstly heat-treating the carbon fiber in an air atmosphere at 450°C for 30 minutes; then adding the pretreated carbon fiber to a solution containing 200 g / L nickel sulfate hexahydrate, 60 g / L nickel chloride hexahydrate, 40 g / L boric acid and 0.1 g / L sodium dodecyl sulfate; when nickel plating, the pH value of the plating solution is maintained at 8.0, the plating solution temperature is 65°C, and the current density is 1.5 A / dm 2 , time is 5min, to obtain nickel-plated carbon fiber.
5. The method for preparing the GW&CF@PEEK composite material according to claim 1, characterized in that: Step S2, the preparation of the hybrid filler includes the following specific steps: adding nickel-plated carbon fiber to a 0.8-1.2wt% benzoxazine / acetone solution, then adding graphene and carbon nanotubes and stirring for 5-7h, the total mass of graphene and carbon nanotubes is 0.95-1.05 times the mass of the nickel-plated carbon fiber, and the mass ratio of graphene to carbon nanotubes is 7-9:1.5-2.5, and finally transferring to an oven for thermal curing after obtaining a slightly moist state through vacuum filtration; the thermal curing procedure is: first thermal curing at 145-155°C for 1.5-2.5h, then thermal curing at 175-185°C for 1.5-2.5h, and finally thermal curing at 205-215°C for 1.5-2.5h; after curing, a hybrid filler is obtained.
6. The method for preparing the GW&CF@PEEK composite material according to claim 5, characterized in that: Step S2, the preparation of the hybrid filler includes the following specific steps: adding nickel-plated carbon fiber to a 1wt% benzoxazine / acetone solution, then adding graphene and carbon nanotubes and stirring for 6 hours, the total mass of graphene and carbon nanotubes is the same as the mass of the nickel-plated carbon fiber, and the mass ratio of graphene to carbon nanotubes is 8:2, and finally transferring to an oven for thermal curing after obtaining a slightly moist state through vacuum filtration; the thermal curing procedure is: first thermal curing at 150°C for 2 hours, then thermal curing at 180°C for 2 hours, and finally thermal curing at 210°C for 2 hours; after curing, a hybrid filler is obtained.
7. The method for preparing the GW&CF@PEEK composite material according to claim 1, characterized in that: Step S3, the temperature of the thermal compression molding is 375-385°C.
8. The method for preparing the GW&CF@PEEK composite material according to claim 1, characterized in that: Step S3, the volume fraction of filler in the composite material is 1.8% to 35%.
9. The method for preparing the GW&CF@PEEK composite material according to claim 8, characterized in that: Step S3, the volume fraction of filler in the composite material is 34.15%.
10. A high-performance GW&CF@PEEK composite material constructed with hybrid heterogeneous fiber fillers, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Hybrid modified composite material with high-conductivity and high-toughness structure and preparation method of hybrid modified composite material
CN106671525A
High-thermal-conductivity conductive carbon fiber polymer-based composite material and preparation method thereof
CN111534049A
High-temperature-resistant electromagnetic shielding function and structure integrated light material and preparation method thereof
CN113024992A
Preparation method of long carbon fiber reinforced composite material for high-strength electromagnetic shielding
CN118085352A
Composite Materials
US20160107739A1